Enhanced conductivity of anatase TiO2 nanowires by La and Co co‐doping. (1st April 2020) - Li, Shanying; Wang, Zhenxin; Yang, Yilong; Li, Jie; Jin, Chi
Abstract : In this work, the conductivity of anatase titanium dioxide (TiO2 ) nanowires was enhanced by lanthanum (La) and cobalt (Co) co‐doping method. The nanowires were synthesised via a facile solvothermal process. The diameter of as‐synthesised nanowires is about 300 nm and length more than 20 μm. The electrical properties were studied based on single nanowire field‐effect transistor; the anatase TiO2 nanowires exhibit n‐type conductivity with mobility of 2.18 cm 2 V −1 S −1 and carrier concentration of 1.95 × 10 18 cm −3 . Doping of rare earth element La and transition element Co can not only reduce bandgap, but also reduce electron–hole recombination and improve carrier concentration. The distinct electrical properties of doped nanowires will open new opportunities for the application of anatase TiO2 semiconductor materials in nanoelectronics devices.